2014
DOI: 10.1088/2041-8205/782/2/l37
|View full text |Cite
|
Sign up to set email alerts
|

PRELIMINARY ANALYSIS OF SOHO/STEREO OBSERVATIONS OF SUNGRAZING COMET ISON (C/2012 S1) AROUND PERIHELION

Abstract: We present photometric and morphological analysis of the behavior of sungrazing comet C/2012 S1 ISON in SOHO and STEREO images around its perihelion on 2013 November 28.779 UT. ISON brightened gradually November 20-26 with a superimposed outburst on November 21.3-23.5. The slope of brightening changed about November 26.7 and was significantly steeper in SOHO's orange and clear filter images until November 27.9 when it began to flatten out, reaching a peak about November 28.1 (r H ≈17R ), then fading before bri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
56
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(58 citation statements)
references
References 19 publications
(34 reference statements)
2
56
0
Order By: Relevance
“…Significant mass loss was not likely triggered by tidal forces, which should not have become significant until the day of perihelion (Knight & Walsh 2013). The recognition of this extreme mass loss helps explain why ISONʼs brightness and morphological behavior in STEREO and Solar and Heliospheric Observatory (SOHO) images in the days before perihelion (Knight & Battams 2014) was akin to that of the small ( < R 50 N m) Kreutz sungrazing comets regularly observed by those telescopes being destroyed as they approach perihelion (Knight et al 2010). While ISONʼs brightness and gas production rates at larger heliocentric distances implied it was large enough to survive insolation despite its small perihelion distance (Knight & Walsh 2013), the largest remaining fragment as it entered the SOHO fields of view was likely quite a bit smaller.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Significant mass loss was not likely triggered by tidal forces, which should not have become significant until the day of perihelion (Knight & Walsh 2013). The recognition of this extreme mass loss helps explain why ISONʼs brightness and morphological behavior in STEREO and Solar and Heliospheric Observatory (SOHO) images in the days before perihelion (Knight & Battams 2014) was akin to that of the small ( < R 50 N m) Kreutz sungrazing comets regularly observed by those telescopes being destroyed as they approach perihelion (Knight et al 2010). While ISONʼs brightness and gas production rates at larger heliocentric distances implied it was large enough to survive insolation despite its small perihelion distance (Knight & Walsh 2013), the largest remaining fragment as it entered the SOHO fields of view was likely quite a bit smaller.…”
Section: Discussionmentioning
confidence: 95%
“…These observations were intended to establish a baseline for comparison with its composition and behavior after perihelion. Since ISON did not survive perihelion (e.g., Knight & Battams 2014;Sekanina & Kracht 2014) this paper represents the totality of our observations. In addition to its destruction near perihelion, ISON was fainter throughout most of its apparition than early expectations, so community data were somewhat limited.…”
Section: Introductionmentioning
confidence: 99%
“…Comet ISONʼs brightness briefly leveled off but then gradually increased through 0.17 au. Inside 0.16 au, comet ISON dramatically brightened, peaking in brightness at 0.051 au just prior to perihelion (Knight & Battams 2014). After perihelion, all spacecraft data showed a steep and accelerating fading.…”
Section: Introductionmentioning
confidence: 96%
“…With a perihelion distance of 0.0125 au (∼2.7 solar radii (R e )), it was predicted to become exceedingly bright, initiating many observing campaigns. The large number of optical observations from ground-and spacebased telescopes made it possible to have a complete view of the mass, size distribution, and evolution of the (sub)micronsized dust in the coma of comet ISON (Knight & Battams 2014;Samarasinha et al 2015). A comprehensive analysis of the light curve revealed that comet ISONʼs intrinsic brightness evolved in cycles of activity between heliocentric distances of 9.4 and 0.7 au, with the duration of the cycles progressively shortening (Sekanina & Kracht 2014).…”
Section: Introductionmentioning
confidence: 99%
“…This very close approach suggested the possibility that the comet Table 2 is only available at the CDS via anonymous ftp to cdsarc.u-strasbg.fr (130.79.128.5) or via http://cdsarc.u-strasbg.fr/viz-bin/qcat?J/A+A/575/A52 could disintegrate near its perihelion, which actually happened: ISON's nucleus did not survive the close approach to the Sun and it totally vanished (Sekanina & Kracht 2014). At the first moment after the perihelion passage, the nucleus -or at least chunks of particles from the nucleus -seemed to have survived, but finally the brightness of ISON faded dramatically in a short period of time (Knight & Battams 2014;Combi et al 2013;Moreno et al 2014). Numerous amateur and professional astronomers tried to recover the comet some days after the perihelion; however, the results were negative (Sako et al 2014).…”
Section: Introductionmentioning
confidence: 99%